1990
DOI: 10.1042/bj2670679
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of the dihydropyridine receptor and the cyclic AMP-binding subunit of an intrinsic protein kinase to the junctional membrane of the transverse tubules of skeletal muscle

Abstract: Junctional transverse tubules (TT) isolated from triads of rabbit skeletal muscle by centrifugation in an ion-free sucrose gradient were compared with membrane subfractions, predominantly derived from the free portion of TT, that had been purified from sarcoplasmic reticulum membrane contaminants by three different methods. The markers used were diagnostic membrane markers and the dihydropyridine (DHP) receptor, which is a specific marker of the junctional membrane of TT. Junctional TT have a high membrane den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 60 publications
4
13
0
Order By: Relevance
“…The results on skeletal muscles have shown that the pump of rabbit fast-twitch muscle localized to the same membrane domain of the transverse tubules to which the dihydropyridine receptor was confined, i.e., to the junctional membrane (Salvatori et al, 1990). In agreement with these findings, PMCA remained bound to the junctional-transverse-tubule component on dissociation of the isolated triads from rabbit skeletal muscles.…”
Section: Y Isupporting
confidence: 70%
See 1 more Smart Citation
“…The results on skeletal muscles have shown that the pump of rabbit fast-twitch muscle localized to the same membrane domain of the transverse tubules to which the dihydropyridine receptor was confined, i.e., to the junctional membrane (Salvatori et al, 1990). In agreement with these findings, PMCA remained bound to the junctional-transverse-tubule component on dissociation of the isolated triads from rabbit skeletal muscles.…”
Section: Y Isupporting
confidence: 70%
“…Studies on rabbit fast-twitch muscle (Salvatori et al, 1990) have shown that junctional transverse tubules differ from free transverse tubules, since they have a very high density of highaffinity dihydropyridine-binding sites. The latter are specifically located at the junctional domain of the transverse tubules, in the gap between the transverse tubules and the terminal cisternae of the SR.…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence for a physical association between PKA and the L-type Ca2+ channel has come from biochemical experiments in which kinase copurifies with the channel in partially purified preparations (30,31). In our experiments, a synthetic peptide representing residues 493-515 ofthe human thyroid AKAP, Ht 31 (23), was found to block kinasedependent potentiation in both mouse and rabbit skeletal muscle myotubes.…”
Section: Discussionmentioning
confidence: 53%
“…[␣- 32 P]ATP Photoaffinity Labeling-Photoaffinity labeling was carried out by the UV irradiation method previously described (25). Dystrophin-DAPs preparations (14 -21 g of protein) or sarcolemma membranes (28 g of protein) were equilibrated with 0.4 M ATP (containing 2 and 4 Ci of [␣-32 P]ATP, respectively) in 100 l of the following different assay environments: 1) Ca-Mg buffer: 25 mM Tris, pH 7.4, 2.5 mM MgCl 2 , 10 M CaCl 2 , and 1 mM dithiothreitol; 2) magnesium buffer: 25 mM Tris, pH 7.4, 2.5 mM MgCl 2 , 2.5 mM EGTA, and 1 mM dithiothreitol; 3) Ca/Mg-free buffer: 25 mM Tris, pH 7.4, 2.5 mM EGTA, 2.5 mM EDTA, and 1 mM dithiothreitol.…”
mentioning
confidence: 99%